Caught in the crossfire: The Uyghurs in America's propaganda war with China. Issue 1 (March 2023) - Gilbert, Simon
The Uyghur people of China's far west are at the centre of a propaganda war between the United States and China. Western media claims about their treatment may well be exaggerated, but the oppression of the Uyghurs is real. In linking its actions to the war on terror, China has created an increasingly violent spiral of repression and resistance. The United States is cynically using this to justify measures that are really about economic competition. Freedom for the Uyghurs can only come as part of a China-wide movement for change.